1992
DOI: 10.1016/0735-1097(92)90130-f
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling and reparation of the cardiovascular system

Abstract: Growth or altered metabolism of nonmyocyte cells (cardiac fibroblasts, vascular smooth muscle and endothelial cells) alters myocardial and vascular structure (remodeling) and function. However, the precise roles of circulating and locally generated factors such as angiotensin II, aldosterone and endothelin that regulate growth and metabolism of nonmyocyte cells have yet to be fully elucidated. Trials of pharmacologic therapy aimed at preventing structural remodeling and repairing altered myocardial structure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
153
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(161 citation statements)
references
References 106 publications
4
153
0
4
Order By: Relevance
“…In the replacement type of fibrosis, fibrous tissue substitutes for vanished necrotic parenchyma. In contrast, the type of fibrosis we documented in the STZ diabetic heart constitutes primary fibrosis resulting from activation of interstitial fibroblasts, similar to what has been documented in rats exposed to aldosterone [27] or Ang II [28]. Cardiac fibrosis impairs left ventricular compliance, causes an abnormal stress relationship and (particularly in conjunction with diminished blood supply) interferes with the electrical stability of the heart [29].…”
Section: Discussionsupporting
confidence: 81%
“…In the replacement type of fibrosis, fibrous tissue substitutes for vanished necrotic parenchyma. In contrast, the type of fibrosis we documented in the STZ diabetic heart constitutes primary fibrosis resulting from activation of interstitial fibroblasts, similar to what has been documented in rats exposed to aldosterone [27] or Ang II [28]. Cardiac fibrosis impairs left ventricular compliance, causes an abnormal stress relationship and (particularly in conjunction with diminished blood supply) interferes with the electrical stability of the heart [29].…”
Section: Discussionsupporting
confidence: 81%
“…3 A partial explanation of biological improvement in LVEF may be upregulation of sarcoplasmic reticulum calcium ATPase (SERCA2), a protein that controls calcium sequestration, and an increase in the relative amount of ␣-myosin heavy chain. 16 In the absence of contractile reserve (ie, when myocytes have been supplanted by replacement fibrosis because of cell death and interstitial remodeling 1,17 ), ventricular function cannot improve by this biological mechanism because there are not enough contractile units. In support of this hypothesis, a previous study of patients with dilated cardiomyopathy taking ␤-blockers showed an inverse relationship between the amount of replacement fibrosis present on endomyocardial biopsy and amount of improvement in LVEF with therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, then the interstitial fibrosis changes the myocardial structure [21,26,27]. In addition, the changes in myocardial structure inhibit myocardial diastolic and systolic function, resulting in cardiac dysfunction [26,27]. The effects of BPS, such as coronary circulation improvement, myocardial and vascular protection [19] and its anti-fibrosis effect on myocardial interstitium [30], have been demonstrated previously.…”
mentioning
confidence: 99%
“…In heart failure with pressure overload, compensated concentric hypertrophy in the left ventricular progresses due to the increase in pressure after overload. As a result, then the interstitial fibrosis changes the myocardial structure [21,26,27]. In addition, the changes in myocardial structure inhibit myocardial diastolic and systolic function, resulting in cardiac dysfunction [26,27].…”
mentioning
confidence: 99%